The Influence of Awareness, Understanding, and Tax Rates Through the Taxation System on Tax Reporting Compliance for Micro, Small, and Medium Enterprises (MSMEs) in Cirebon Regency - Adistie Rizky Berliani; Diana Pratiwi; Fredlina Adelia; Dev Anand (Indonesian Journal of Business Analytics, 2024)
Economic growth from year to year continues to increase, this should be in line with the increase in tax revenue. This can affect the state budget by 84% because it is financed from taxation sources.This research aims to determine the influence of awareness, understanding, and tax rates through the taxation system on tax reporting compliance for micro, small, and medium enterprises (MSMEs) in the Cirebon Regency. This research uses a quantitative descriptive analysis approach to produce conclusions. Data collection is carried out through KPP Pratama Cirebon Dua. Based on the researchers' findings, the calculated t value for each variable from the influence of awareness, understanding, tax rates, and digitalization of the tax system is 12.219, 5,940, 6,779, and 8.127, with an F table value of 1.985. Based on this, the level of tax reporting compliance is positively correlated with the tax rate variable. The level of tax reporting compliance is positively correlated with the taxpayer's understanding of taxation. The level of tax reporting compliance is positively correlated with the tax awareness variable of MSME actors. The level of tax reporting compliance is positively correlated with the variable digitalization of the tax system. The findings of this test show that MSME taxpayers can disclose their tax obligations more quickly and without having to come to the tax service office if the DGT's online services are improved